Aplicaciones Interdisciplinarias entre Física, Medicina y Psicología - De la Roca-Chiapas, José María; Córdova-Fraga, Teodoro; Córdova-Fraga, Teodoro; Barbosa Sabanero, Gloria; Barbosa Sabanero, Gloria; Macías de la Cruz, J. Humberto; Macías de la Cruz, J. Humberto; Cano, M. E.; Cano, M. E.; Pacheco Hain, Aleph; Pacheco Hain, Aleph; Cisneros, Antonio; et al. (Acta Universitaria, 2009)
This paper presents two lines of research linking physics, medicine and psychology. The first is the mechanical magnetogastrography used to measure gastric emptying and peristaltic contractions and its relationship to evaluate the physiological behavior related to emotional states. The second is the psicomagnetobiology as a model of induction of cancerstress and biochemical markers that enable the comparison, spectroscopic characterization and imaging using a magnetic scanner, which could be used in the diagnosis and the use of hyperthermia as a treatment for cancer. The Mecano-magnetogastrography is a useful technique for measuring gastric emptying, which is not invasive, does not use ionizing radiation and demonstrates that through the reading of the magnetic fields of magnetic trace ringested can obtain information on gastric emptying and peristaltic contraction, presented reproducible results. In terms of research we call psicomagnetobiology has been used for induction of cancer with N-methyl-N-nitrosourea, resulting in breast cancer 58% of rats.
Keywords: Array; Array; Array